The adventures of Strawberry Shortcake and her friends - Wallner, Alexandra; Llimona, Mercedes (New York : Random House, 1980)
The Strawberry Kids make an unusual scarecrow to frighten birds away from their crops.
Keywords: Scarecrows -- Fiction